Penerapan Analisis Cluster Hybrid untuk Pengelompokan Kabupaten/Kota di Provinsi Jawa Barat Berdasarkan Indikator Kemiskinan Tahun 2022 - Wardah Muna Fauziyah; Anneke Iswani Achmad (Bandung Conference Series: Statistics, 2023)
Abstract. Hybrid cluster analysis is a combination of hierarchical and non-hierarchical clusters, which has a goal as an alternative method. The advantage of hybrid cluster analysis is that it can determine k-clusters for the process of making non-hierarchical clusters through the results of making hierarchical cluster methods, which will produce the right k-clusters. With the advantages of the hybrid cluster analysis, this research will combine the single linkage method with k-means, then the ward method with k-means. The purpose of this study was to determine the grouping of districts/cities in West Java Province with the most optimal combination method based on poverty in 2022. Based on the results of hybrid cluster analysis using a combination of k-means clusters and single linkage, 4 clusters were obtained. While the results of hybrid cluster analysis using a combination of k-means clusters and the ward method obtained 3 clusters. Among the hybrid cluster analysis using a combination of k-means and single linkage clusters as well as a combination of k-means cluster and ward method, it can be said that the method with a combination of k-means and single linkage is the best or most optimal method with the smallest standard deviation ratio value of 88.38%. Abstrak. Analisis cluster hybrid merupakan kombinasi antara cluster hierarki dan non-hierarki, dimana memiliki tujuan sebagai metode alternatif. Kelebihan analisis cluster hybrid adalah dapat menentukan k-klaster untuk proses pembuatan cluster non-hierarki melalui hasil dari pembuatan cluster metode hierarki, dimana akan menghasilkan k-klaster yang tepat. Dengan kelebihan analisis cluster hybrid tersebut, maka dalam penelitian ini akan mengkombinasikan metode single linkage dengan k-means, kemudian ward method dengan k-means. Tujuan penelitian ini adalah dapat mengetahui pengelompokan Kabupaten/Kota di Provinsi Jawa Barat dengan metode kombinasi yang paling optimal berdasarkan kemiskinan tahun 2022. Berdasarkan hasil analisis cluster hybrid dengan menggunakan kombinasi cluster k-means dan single linkage diperoleh 4 cluster. Sedangkan hasil analisis cluster hybrid dengan menggunakan kombinasi cluster k-means dan ward method diperoleh 3 cluster. Diantara analisis cluster hybrid dengan menggunakan kombinasi cluster k-means dan single linkage serta kombinasi cluster k-means dan ward method, dapat dikatakan bahwa metode dengan kombinasi k-means dan single linkage merupakan metode terbaik atau yang paling optimal dengan nilai rasio simpangan baku terkecil yaitu sebesar 88,38%.